Effect of Probiotics on Allergic Rhinitis: A Randomized, Controlled, Clinical Trial: - Sadeghi-Shabestari, Mahnaz; Jabbari Moghaddam, Yalda; Rezapoor, Hasan; Sohrabpour, Mojataba (Galen Medical Journal, 2020)
Background: Allergic rhinitis (AR) is one of the most common diseases in the world and affects about 10-50% of the general population. Probiotics are live microorganisms that help the normal state of the intestine, and if prescribed correctly, they can stimulate the mucosal immune system to prevent inflammatory symptoms of allergy and atopy. The present study aims to investigate the role of probiotics in the treatment of AR when added to standard therapy as adjuvant agents. Materials and Methods: In this clinical trial study, 28 patients older than 15 years with AR randomly divided into probiotics and control groups. The probiotics group received standard therapy for AR accompanied by probiotic capsules every 12 hours for eight weeks, whereas the control group received standard therapy for AR with placebo capsules as the same protocol. Data were analyzed using SPSS Version 23 (IBM Corporation, Armonk, NY, USA) and, the P-value less than 0.05 was considered statistically significant. Results: In the probiotics group, 14.3% of patients had sneezing at the baseline, which significantly decreased to 4.6% (P<0.01). Also, the necessity for nasal and oral corticosteroids after treatment with probiotics in the probiotics group was less than the control group (P<0.01). Although cough, nasal discharge, conchae hypertrophy, and night sleep disorders reduced after treatment with probiotics, this reduction was not statistically significant between the two groups. Conclusion: Based on the results of this clinical trial, the use of probiotics had no significant effect on the outcome of patients with AR. [GMJ.2020;9:e1918]